GROUP DECISION SUPPORT SYSTEM PADA PENYELEKSIAN ATLET TAEKWONDO - Ni Luh Putu Merawati; La Dzunnafi Arridlwany; Ismarmiaty Ismarmiaty; Ria Rismayati (Jurnal Teknoinfo, 2023)
Taekwondo is a popular martial art sport that originated in Korea that developed in Indonesia in 1975 under Taekwondo Indonesia where the management of provincial activities was supervised by the Provincial Board. This study aims to assist the needs of multi-criteria decision making with the concept of Group Decision Support Systems for selecting Taekwondo athletes in West Nusa Tenggara. This system involves two decision makers, namely the Chief Executive of Pengprov and the Trainer. The method used in calculating decision making is the Weighted Product and Borda methods. The criteria used are geup, weight and age on the cost criteria, and medal criteria, charter, height, push ups, sit ups and balke on the benefits criteria. The data used in this study are 30 alternative data of Taekwondo members who are in the men's division. The stages of the research include: problem analysis, data collection, data initialization, implementation of the Weight Product method, implementation of the Borda method and analysis of the results & drawing conclusions. The results provide decision recommendations for the top 10 best assessments consisting of A25, A19, A14, A09, A26, A28, A01, A04, A07 and A06. Furthermore, the results of the analysis using the division of class categories based on body weight produce alternative data that are not evenly distributed in each class category. This provides more information to decision makers by considering the results of athlete rankings with the needs of prospective athletes in the weight class category.GROUP DECISION SUPPORT SYSTEM PADA PENYELEKSIAN ATLET TAEKWONDO